Androgens in peri- and postmenopausal women - Skałba, Piotr; Dąbkowska-Huć, Anna (Menopause Review/Przegląd Menopauzalny, 2006)
androgens, testosterone, menopause, polycystic ovary syndrome, ovarian tumours, androgen treatment